Population structure and insecticide resistance status of Tuta absoluta populations from Turkey - İnak, Emre; Özdemir, Esengül; Atış, Abdullah Emre; Zelyüt, Filiz Randa; İnak, Arda; Demir, Ünver; Raditakis, Emmanouil; Vontas, John (John Wiley and Sons Ltd, 2021)
BACKGROUND: Tuta absoluta is a devastating pest in tomato production areas worldwide. After its first introduction to Turkey in 2009, it quickly became the major pest of tomato-growing areas. Although some biocontrol agents have been used, especially in greenhouses, the main control of T. absoluta relies heavily on chemical insecticides. However, failure in chemical control has often been reported due to resistance development. In this study, we investigated (i) the population structure of 22 T. absoluta populations across Turkey by analysing haplotypes, based on the cytochrome oxidase subunit I gene; (ii) the efficacy of three registered insecticides from different classes (metaflumizone, chlorantraniliprole and spinosad) in real field-greenhouse conditions; and (iii) the geographic distribution of target-site mutations associated with insecticide resistance. RESULTS: The efficacy of spinosad was higher than that of chlorantraniliprole and metaflumizone in the greenhouse trials, as documented by the mortality rates obtained, up to 14 days post application. Known resistance mutations in ryanodine receptors (RyR) (i.e. the I4790M/K and G4946E), nicotinic acetylcholine receptors (G275E), acetylcholinesterases (A201S) and voltage-gated sodium channels (F1845Y and V1848I) were found at various frequencies across the populations genotyped. The I4790K diamide resistance mutation in the RyR has been reported for the first time in T. absoluta populations. Although a total of eight haplotypes were found, the overall mean genetic distance was lower than 0.001, indicating the high genetic homogeneity among Turkish T. absoluta populations. CONCLUSION: The results will contribute to design area-wide resistance management programs in T. absoluta control in Turkey. However, more monitoring studies are needed to implement evidence-based insecticide resistance management strategies in the frame of integrated pest management.
Keywords: insecticide resistance; Nicotinic acetylcholine receptor; Resistance mutations; Ryanodine receptors; Tuta absoluta